QUALITY OF SERVICE IN PASSPORT APPLICATIONS AT CLASS I NON TPI BOGOR IMMIGRATION OFFICE - Panji Hendrarso (Adisam Publisher, 2024)
Improvements to public service systems and procedures leading to excellent public service provided by officials/bureaucrats to the public should be carried out with full attention so that it is hoped that it will generate positive views from both customers and officials providing services. Therefore, the implementation of public services must be carried out and run based on service principles in accordance with applicable regulations. This is qualitative research with a case study approach. Data collection was carried out using semi-structured interviews with 15 passport applicants, participant observation and documentation. The results of this research show that the quality of public services at the Bogor Class 1 Immigration Office has experienced a significant increase, and is in accordance with service standards according to the Decree of the Minister for Administrative Reform namely Kep. MENPAN No. 63/KEP/M.PAN/7/2003 which includes service procedures, completion time, service costs, service products, facilities and infrastructure, and competency of service officers.